Preventing SARS-CoV-2 infection by blocking a tissue serine protease. (June 2020) - Jankousky, Katherine C.; Schultz, Jonathan; Windham, Samuel; Henao-Martínez, Andrés F.; Franco-Paredes, Carlos; Shapiro, Leland
Currently, there are no proven pharmacologic interventions to reduce the clinical impact and prevent complications of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection, the cause of the ongoing Coronavirus Disease of 2019 (COVID-19) pandemic. Selecting specific pharmacological targets for the treatment of viral pathogens has traditionally relied in blockage of specific steps in their replicative lifecycle in human cells. However, an alternative approach is reducing the molecular cleavage of the viral surface spike protein of SARS-CoV-2 to prevent viral entry into epithelial cells.